Two Structurally Characterized Conformational Isomers with Different C−P Bonds. Issue 50 (21st July 2017) - Roy, Sudipta; Mondal, Kartik Chandra; Kundu, Subrata; Li, Bin; Schürmann, Christian J.; Dutta, Sayan; Koley, Debasis; Herbst‐Irmer, Regine; Stalke, Dietmar; Roesky, Herbert W.
Abstract: The cyclic alkyl(amino) carbene (cAAC) bonded chlorophosphinidene (cAAC)P−Cl (2 /2' ) was isolated from the direct reaction between cAAC and phosphorus trichloride (PCl3 ). Compound2 /2' has been characterized by NMR spectroscopy and mass spectrometry. 31 P NMR investigations [ δ ≈160 ppm (major) and δ ≈130 ppm (minor)] reveal that there are two different P environments of the P−Cl unit. X‐ray single‐crystal determination suggests a co‐crystallization of two conformational isomers of (cAAC)P−Cl (2 /2' ); the major compound possessing a cAAC−PCl unit with CcAAC −P 1.75 Å. This C−P bond length is very close to that of (NHC)2 P2 [NHC= N ‐heterocyclic carbene]. The residual density can be interpreted as a conformational isomer with a shorter CcAAC −P bond similar to a non‐conjugated phosphaalkene [R−P=CR2 ]. Our study shows an unprecedented example of two conformational isomers with different Ccarbene −element bonds. Additionally, Br (3c /3c' ), I (4c /4c' ), and H (5c /5c' ) analogues [(Me2 ‐cAAC)P−X; X=Br (3 ), I (4 ), H (5 )] of2c /2c' [(Me2 ‐cAAC)P−Cl] were also synthesized and characterized by NMR spectroscopy suggesting similar equilibrium in solution. The unique property of cAAC and the required electronegativity of the X (X=Cl, Br, I, and H) atom play a crucial role for the existence of the two isomers which were further studied by theoretical calculations. Abstract : An unprecedented dual bonding situation is demonstrated by the cyclic alkyl(amino) carbene (cAAC) bound chlorophosphinidene (cAAC)P‐Cl (2/2' ). The conformational form with a C−P bond length of 1.75 Å is the major conformer (2 ) possessing a donor–acceptor coordinate (CcAAC →P−Cl) bond. The minor conformer (2' ) with a C−P bond length of 1.61 Å contains a double bond (CcAAC =P−Cl). The presence of two resonance forms has been confirmed by NMR studies. The bonding situation and stability of2/2' have been studied by theoretical calculations.